Propensity score matching analysis of valve-sparing versus aortic root replacement in type A aortic dissection patients - Ling Chen; Yichao Pan; Huaijian Zhang; Yi Chen; Chunsheng Wang; Zhihuang Qiu; Heng Lu; Liangwan Chen (Nature Communications)
Abstract This study compared long-term survival and reintervention rates between Valve-Sparing Root Replacement (VSRR, n = 244) and Aortic Root Replacement (ARR, n = 499) in 743 patients undergoing Type A acute aortic dissection (AAD), given the lack of prospective comparative data. Multivariable analysis is identifying advanced age, high Body Mass Index (BMI), Marfan syndrome, severe aortic regurgitation, bicuspid aortic valve, increased aortic root diameter, and reduced aortic cross-clamp time (ACC) as significant factors associated with ARR. After Propensity Score Matching (PSM), VSRR is showing significantly higher 5-year survival rates than ARR (80.2% vs. 64.1%, P = 0.001), validated by Inverse Probability of Treatment Weighting (IPTW) analysis. Reintervention rates are being found comparable, with endocarditis more prevalent in ARR and aortic regurgitation in VSRR. Subgroup analysis indicated that patients aged less than 60 years and those with a BMI greater than 24 in the VSRR group exhibited significantly improved survival probabilities compared to the ARR group. These findings support the wider utilization of valve-sparing root replacement (VSRR) in appropriately selected patients, highlighting its potential advantages for suitable candidates.